Rewarding in International Law - Anne van Aaken; Betül Simsek (University of Hamburg, Institute of Law and Economics (ILE), 2021)
The question of why states comply with international law has long been at the forefront of international law and international relations scholarship. The compliance discussion has largely focused on negative incentives for states to comply. We argue that there is another, undertheorized mechanism: rewarding. We provide a typology as well as illustrations of how rewards can be applied. Furthermore, we explore the ratio nale, the potential, and the limitations of rewarding, drawing on rationalist as well as psychological approaches. Both give ample arguments to make more use of rewarding in international law.
Keywords: 340